Influence of Indo-Islamic Architecture - Mumbai Archive Project Team (Jio Institute, 2024)
The architecture of the Aga Khan Maqbara is influenced by several Indo-Islamic structures, especially the Taj Mahal at Agra and the tombs of the Qutub Shahi dynasty of Golkonda (Hyderabad). Its resemblance to the Taj Mahal has led to it being dubbed the ‘Taj Mahal of Mumbai’.